2008
DOI: 10.1007/s11458-008-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation time/temperature dependence of some thermoplastics-modified thermosetting systems

Abstract: The phase separation processes of various thermoplastics-modified thermosetting systems which show upper critical solution temperature (UCST) or lower critical solution temperature (LCST) were studied with emphasis on the temperature dependency of the phase separation times. It was found that the phase separation time-temperature relationship follows the Arrhenius equation. The cure-induced phase separation activation energy E a (ps) generated from the equation is independent of the method used to measure phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Several studies have been reported. [6][7][8] Pascault et al gave a clear relationship between rheological prole and phase separation in polyetherimide modied epoxy systems; they observe an increase in complex viscosity for phase inverted blends. 9 Kim and Char observed an early increase in viscosity due to the phase separation of thermoplastic from the thermoset matrix followed by a decrease due to the destruction of the phase, before the abrupt viscosity increase due to epoxy-amine reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported. [6][7][8] Pascault et al gave a clear relationship between rheological prole and phase separation in polyetherimide modied epoxy systems; they observe an increase in complex viscosity for phase inverted blends. 9 Kim and Char observed an early increase in viscosity due to the phase separation of thermoplastic from the thermoset matrix followed by a decrease due to the destruction of the phase, before the abrupt viscosity increase due to epoxy-amine reaction.…”
Section: Introductionmentioning
confidence: 99%